Oxidized Forms of Ergothioneine Are Substrates for Mammalian Thioredoxin Reductase - Kaelyn A. Jenny; Gracyn Mose; Daniel J. Haupt; Robert J. Hondal (MDPI AG, 2022)
Ergothioneine (EGT) is a sulfur-containing amino acid analog that is biosynthesized in fungi and bacteria, accumulated in plants, and ingested by humans where it is concentrated in tissues under oxidative stress. While the physiological function of EGT is not yet fully understood, EGT is a potent antioxidant in vitro. Here we report that oxidized forms of EGT, EGT-disulfide (ESSE) and 5-oxo-EGT, can be reduced by the selenoenzyme mammalian thioredoxin reductase (Sec-TrxR). ESSE and 5-oxo-EGT are formed upon reaction with biologically relevant reactive oxygen species. We found that glutathione reductase (GR) can reduce ESSE, but only with the aid of glutathione (GSH). The reduction of ESSE by TrxR was found to be selenium dependent, with non-selenium-containing TrxR enzymes having little or no ability to reduce ESSE. In comparing the reduction of ESSE by Sec-TrxR in the presence of thioredoxin to that of GR/GSH, we find that the glutathione system is 10-fold more efficient, but Sec-TrxR has the advantage of being able to reduce both ESSE and 5-oxo-EGT directly. This represents the first discovered direct enzymatic recycling system for oxidized forms of EGT. Based on our in vitro results, the thioredoxin system may be important for EGT redox biology and requires further in vivo investigation.